STRATEGI INTEGRASI PENDIDIKAN BUDI PEKERTI DALAM PEMBELAJARAN BERBASIS KOMPETENSI - Suwarna Suwarna (LPMPP Universitas Negeri Yogyakarta, 2007)
Character education represents one of the principal loads in theimplementation of the Competency-Based Curriculum (Balitbang,2002) and it is carried out by means of an integrated learningapproach, i.e., by integrating it into all class subjects. Problems arisebecause not all teachers possess the potential sensitivity adequate foridentifying and analyzing materials for character education in thelearning materials or lesson books used. The teachers tend to merelyteach whatever is explicit in the learning materials while thematerials for character education implicit in the learning materialsare not perceived and revealed. As a result, the character educationimplied is not worked out and does not reach the learner.To solve the problem, certain strategies need to be employed incarrying out character education integrated in the competency-basedclass subjects. The strategies cover presentation and learningstrategies, the former further covering implicit and explicit strategiesand the latter further covering deductive and inductive strategies.The strategies could also be combined into implicit-deductive,implicit-inductive, explicit-deductive, and explicit-inductive ones.The identification, interpretation, and analysis of materials forcharacter education should be made to fit the local cultural context(implying Contextual Teaching and Learning or CTL).